Wearable breathing barriers (masks) to reduce droplet transmission of COVID-19 (International Journal of First Aid Education)
People trained in first aid, may be called upon to provide immediate and long-term care because of their competencies, especially as traditional healthcare workers may be limited or not available. Providing care for a person with Covid-19 increases the risk to the person for disease transmission and requires a breathing barrier with a filter that is better than the common procedural mask or cloth mask. First aid educators are in a unique position within the community and organized health care to provide support for the development of breathing barrier construction that could be used by first aiders or other healthcare workers (HCW) when commercially made breathing respirators or filters are not available. This review and recommendations provides rationale and teaching elements for building the highest quality mask with given resources.